Resistance Against Leishmania major Infection Depends on Microbiota-Guided Macrophage Activation - Lopes, Mateus Eustáquio; dos Santos, Liliane Martins; Sacks, David; Vieira, Leda Quercia; Carneiro, Matheus B. (Frontiers in Immunology, 2021)
Innate immune cells present a dual role during leishmaniasis: they constitute the first line of host defense but are also the main host cells for the parasite. Response against the infection that results in the control of parasite growth and lesion healing depends on activation of macrophages into a classical activated phenotype. We report an essential role for the microbiota in driving macrophage and monocyte-derived macrophage activation towards a resistance phenotype against Leishmania major infection in mice. Both germ-free and dysbiotic mice showed a higher number of myeloid innate cells in lesions and increased number of infected cells, mainly dermal resident and inflammatory macrophages. Despite developing a Th1 immune response characterized by the same levels of IFN- production as the conventional mice, germ-free mice presented reduced numbers of iNOS+ macrophages at the peak of infection. Absence or disturbance of host microbiota impaired the capacity of bone marrow-derived macrophage to be activated for Leishmania killing in vitro, even when stimulated by Th1 cytokines. These cells presented reduced expression of inos mRNA, and diminished production of microbicidal molecules, such as ROS, while presenting a permissive activation status, characterized by increased expression of arginase I and il-10 mRNA and higher arginase activity. Colonization of germ-free mice with complete microbiota from conventional mice rescued their ability to control the infection. This study demonstrates the essential role of host microbiota on innate immune response against L. major infection, driving host macrophages to a resistance phenotype.